DECISION OF FRAUD DISCLOSURE IN THE INDONESIAN REGIONAL GOVERNMENT - Johan Arifin; Sheila Hikma Ariefadisya; Chivalrind Ghanevi Ayuntari (Riset Akuntansi dan Keuangan Indonesia, 2020)
AbstractThe objective of this study was to examine the potential factors affecting employees to perform whistleblowing in Indonesian regional government level. The examined factors included supervisor support, protection, compensation and the level of fraud severity.This study was conducted by testing 130 civil servants who have worked in a number of regions in Indonesia. The test was done by handing out questionnaires that consisted of some questions and two case studies. The participants were asked to answer one of the available  five answer choices which were related to the decision of fraud disclosure in regional government. The result showed that employees were willing to disclose any fraud in the workplace if they received sufficient supervisor support, protections and considered that the level of fraud was serious. However, it was found that compensation did not affect the employees to perform whistleblowing.Keywords: Whistleblowing, Wrongdoing, Supervisor Support, Protection, Compensation.